Analysis of Factors Causing High Referral Rates at Primary Health Center in the JKN Era: A Literature Review - Syamira Nurjannah Ramadhani (Media Gizi Kesmas, 2020)
Background: The implementation of the referral system in the JKN era is not yet running optimally due to an increase in the number of referrals from FKTP to FKRTL. The applicable standard for referral ratio is 15%, from the total BPJS patient visits every month, but the above standard reference ratio is still found in various health centers in Indonesia.Objectives: This study aims to determine the factors that cause the high number of referrals in health centers in the JKN era Methods: This research is a type of literature review where the articles obtained are sourced from Google Scholar as a database. There were 13 articles published from 2010 to 2020 that were considered relevant to the research topicResults: Research shows that Primary Health Center with increased referral are caused by low quality and quantity of human resources, lack of SOP, lack of complete and adequate facilities and infrastructure, medical indications suffered by patients beyond the ability of Primary Health Center, incompleteness of medicines and medical materials and lack of understanding patients with the referral systemConclusions: Factors causing the high number of referrals in health centers in the JKN era included the availability of human resources, the existence of SOPs, the completeness of facilities and infrastructure, types of medical indications, availability of medicines and patient behavior